Synthesis of the types and trends of review articles - Zhai, Xiuwen; Razali, Abu Bakar; Sulaiman, Tajulripin (Hindawi, 2022)
The practice of review writing is an essential component of postgraduate students’ academic studies for graduation requirement and especially for those who are undergoing their postgraduate studies by theses by publication. However, very few studies have focused on review genres. In this review, the researchers would like to offer an overview of different types of review articles and identify the trend in the development of the review article genre. The researchers of this study employed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. They identified the published articles specific to the review genres via a structured keyword search in Web of Science, Scopus, and Google Scholar (from the years 2019–2022). A mixed analysis approach (e.g., qualitative analysis combined with quantitative analysis) was conducted to further examine the selected articles using the data visualization software CiteSpace. The results showcased that there were currently a limited number of review types in social science disciplines. The researchers call for more effort to discover new models for writing review genres in the EFL/ESL context. This study also discusses the theoretical and practical implications.